The co-movements along the forward curve of natural gas futures: a structural view - Fabrizio Spargoli; Paolo Zagaglia (Bank of Finland, 2008)
We study the term structure implications of the fiscal theory of price level determination. We introduce the intertemporal budget constraint of the government in a general equilibrium model in continuous time. Fiscal policy is set according to a simple rule whereby taxes react proportionally to real debt. We show how to solve for the prices of real and nominal zero coupon bonds.
URN:NBN:fi:bof-20140807184
Keywords: G12; 330; bond pricing; fiscal policy; mathematical methods